Teachers’ Narratives on Strategies for Enhancing Scientific Curiosity in a Public Secondary School - Nerio, Jose Marie; Linaugo, Joji; Sulaeman, Nurul F. (Jurnal Pendidikan IPA Indonesia, 2025)
Teachers’ narratives on strategies for enhancing scientific curiosity in secondary public schools are significant, particularly for uncovering the different approaches science teachers use to cultivate students' curiosity in science education. This research aimed to uncover teachers' narratives about strategies to enhance students' scientific curiosity. This study also examined science teachers' perspectives on scientific curiosity. It utilized a qualitative research design, specifically a narrative inquiry approach. The data were obtained from four junior secondary school science teachers at one school in the central Philippines using a triangulation method: one-on-one interviews, essays, and focus group discussions. The involved conversation partners were determined using a purposeful sampling. Four themes were forwarded based on the original statements of the conversation partners: pedagogical approaches to enhance curiosity, including fostering an active learning environment and resilient instruction to meet students' needs; instructional challenges and difficulties; and scientific curiosity as a curiosity-driven inquiry. This study highlights integrating pedagogical strategies that enhance students' scientific curiosity into daily instruction. Schools should design professional development programs that emphasize curiosity-enhancing teaching methods. The research findings have major consequences for how teachers implement and use pedagogical approaches that cultivate scientific curiosity and for how students engage in the lesson based on the strategies teachers use.